2020
DOI: 10.1007/s40194-020-00856-9
|View full text |Cite
|
Sign up to set email alerts
|

WeldForming: a new inline process combination to improve weld seam properties

Abstract: The high heat input during fusion welding leads to transformations of the microstructure in the area subjected to welding, mostly resulting in a heterogene crystalline structure and an overall deterioration of the mechanical properties. To reduce the detrimental effect, posttreatment processes which are typically separated from the actual welding process are state of the art. The present work shows the new methodology, WeldForming, which intends to eliminate subsequent treatment processes. The new in-line proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The first strategy (Figure 2a) includes the process combination of welding and forming a single layer single-bead. This process was examined in [8] and the obtained experimental data was used to develop and validate a simulation model for the simple process combination. The simulation model was calibrated by thermal measurements with thermo couples regarding cooling during welding and forming.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first strategy (Figure 2a) includes the process combination of welding and forming a single layer single-bead. This process was examined in [8] and the obtained experimental data was used to develop and validate a simulation model for the simple process combination. The simulation model was calibrated by thermal measurements with thermo couples regarding cooling during welding and forming.…”
Section: Methodsmentioning
confidence: 99%
“…However, this is preliminary work and the results indicate further machining procedures are required. A study by Adams et al on the inline WeldForming process exhibits validation of the numerical model followed by microstructural analysis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing the ratio increases the weld joint's strength during tensile tests. According to many researches [ 13 16 ], the degree and extent of softening in part of the HAZ are mostly related to the base material, the cooling time t 8/5 [s], and thus the welding procedures [ 23 – 26 ]. The width of the HAZ soft zone expands linearly with an increase in the t 8/5 [ 17 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Grain refinement is an important method to improve the mechanical properties of a TIG weld. The single plastic deformation through the WeldForming process was used by Adams et al [ 26 ] to improve the weld seam properties of HSSs. Our previous work [ 27 ] demonstrated that the plastic deformation combined with frequent vibrations during thermomechanical welding (TMW) can refine the microstructure of the FZ by occurring recrystallisation processes.…”
Section: Introductionmentioning
confidence: 99%